Research Trends on Green Campus in Southeast Asia: A Bibliometric Review - Dwica Hanifah Rizal; Gusman Nawanir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to uncover previous research flows and predict future research directions related to research trends on green campuses in Southeast Asia. This review uses a bibliometric approach using 1,761 journals from WoS. Two science mapping approaches (i.e., co-citation analysis and co-word analysis) are conducted to investigate past research trends and future research directions on green campuses. The trend of articles in the past has focused on sustainability in higher education environments by considering behavioral factors that influence technology adoption. In the future, articles on green campuses in Southeast Asia will emphasize management frameworks and student engagement, as well as managing renewable energy systems in sustainable practices. This study will benefit researchers, practitioners, and the public by enhancing understanding and implementing sustainability on green campuses in Southeast Asia. In the future, this article will emphasize a sustainable framework through renewable energy, sustainable behavior, collaboration, and operational management. This study provides valuable insights into green campuses, particularly in Southeast Asia, with guidance for policies and interventions that encourage behaviors to reduce environmental impacts. The article promotes sustainable practices and emphasizes the role of green campuses in shaping an environmentally conscious generation.